Coinfection of porcine deltacoronavirus and porcine epidemic diarrhea virus increases disease severity, cell trophism and earlier upregulation of IFN-α and IL12 - Kepalee Saeng-chuto (Nature Portfolio, 2021)
Abstract Porcine epidemic diarrhea virus (PEDV) and porcine deltacoronavirus (PDCoV) cause an enteric disease characterized by diarrhea clinically indistinguishable. Both viruses are simultaneously detected in clinical cases, but a study involving the co-infection has not been reported. The study was therefore conducted to investigate the disease severity following a co-infection with PEDV and PDCoV. In the study, 4-day-old pigs were orally inoculated with PEDV and PDCoV, either alone or in combination. Following challenge, fecal score was monitored on a daily basis. Fecal swabs were collected and assayed for the presence of viruses. Three pigs per group were necropsied at 3 and 5 days post inoculation (dpi). Microscopic lesions and villous height to crypt depth (VH:CD) ratio, together with the presence of PEDV and PDCoV antigens, were evaluated in small intestinal tissues. Expressions of interferon alpha (IFN-α) and interleukin 12 (IL12) were investigated in small intestinal mucosa. The findings indicated that coinoculation increased the disease severity, demonstrated by significantly prolonged fecal score and virus shedding and decreasing VH:CD ratio in the jejunum compared with pigs inoculated with either PEDV or PDCoV alone. Notably, in single-inoculated groups, PEDV and PDCoV antigens were detected only in villous enterocytes wile in the coinoculated group, PDCoV antigen was detected in both villous enterocytes and crypts. IFN-α and IL12 were significantly up-regulated in coinoculated groups in comparison with single-inoculated groups. In conclusion, co-infection with PEDV and PDCoV exacerbate clinical signs and have a synergetic on the regulatory effect inflammatory cytokines compared to a single infection with either virus.